Effect of Phototherapy On the Serum Calcium Level in Term Neonates with Indirect Hyperbilirubinemia: Phototherapy in Term Neonates with Indirect Hyperbilirubinemia - Pervaiz, Ghanwa; Alvi, Misbah Ayub; Abbas, Zuraira; Malik, Minahil Ilyas; Abbas, Mohsin; Anwar, Waqar (Pakistan Journal of Health Sciences, 2025)
Normal calcium levels in neonates are crucial for preventing hypocalcemia. Phototherapy disrupts melatonin secretion, enhancing cortisol-induced hypocalcemia and urinary calcium excretion. Objectives: To determine the effect of phototherapy on serum calcium levels and its association with the incidence of hypocalcemia in term neonates with indirect hyperbilirubinemia. Methods: A descriptive case series was carried out in the Department of Pediatrics, Islamic Teaching Hospital, Sialkot, between Nov 5, 2023, and April 4, 2024. A total of 134 newborns who met the study’s inclusion and exclusion criteria were enrolled. Demographic information, including name, age, sex, weight, and address, was noted. Three milliliters of venous blood were drawn before the commencement of conventional phototherapy and following forty-eight hours of nonstop phototherapy. The sample was subsequently transferred to a laboratory for the measurement of calcium and serum indirect bilirubin levels. All data was collected through a well-designed proforma. Results: A Total of 134 patients, 77 (57.5%) belonged to the age category of 0-15 days, while 57 (42.5%) belonged to the age group of 16-28 days. The mean age of the patients was determined to be 14.32 ± 5.25 days. There were 66 (49.3%) female and 68 (50.7%) male. The percentage of hypocalcemia was 31 (23.1%) in term neonates receiving phototherapy for indirect hyperbilirubinemia. Conclusions: It was concluded that the percentage of hypocalcemia was 31 (23.1%) in term neonates receiving phototherapy for indirect hyperbilirubinemia. Phototherapy effectively reduces serum bilirubin levels but is associated with a significant decline in serum calcium, suggesting a potential risk of hypocalcemia in neonates.